New characteristics and hedonic price index numbers - Ian Crawford; J. Peter Neary (Center for Economic Studies and ifo Institute (CESifo), 2019)
Changes in product characteristics on the extensive margin are an important and hitherto neglected dimension of quality change. Standard techniques for quality-adjusting price indices cannot handle such changes satisfactorily, which leads to an economically and statistically significant bias in the measurement of prices and real output. We combine theoretical insights from index numbers and demand for characteristics to develop a new method for incorporating changes on the extensive characteristic margin. Applied to data on new car sales in the U.K., our method leads to revisions in estimated inflation rates for this commodity group that are both plausible and quantitatively important.
Keywords: C90; C91; C92; D03; 330; extensive and intensive margins of consumption; characteristics model; quality change; Sato-Vartia-Feenstra index numbers